2021
DOI: 10.1021/acs.chemmater.1c01401
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments for Optimization of Polyoxometalate Syntheses

Abstract: Design of experiments (DOE) is a key method for optimizing physical processes by altering multiple variables at once to assess their effect. In chemistry, DOE explores a wider parameter space than the dominant “One Factor at a Time” (OFAT) method providing greater opportunity to explore the factors that can be used to optimize yield, purity, and to explore chemical space for new compounds. One area of chemistry that suffers from low yields and poor reproducibility but is full of hard to predict and interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…DoE has been used extensively in the optimization of chemical processes, particularly in pharmaceutical and fine chemical settings. DoE is often used for studies relating to enhancing the yield and purity of particular products but is also used for drug formulations and delivery, analytical method development, and more. This is because there are numerous and undisputed benefits to the use of DoE for experimental parameter screening and optimization, especially when compared with traditional human intuition-guided experimentation. With the rise of user-friendly software packages and the increased awareness of the chemical community, there has been a large uptake of this statistical method in recent years, although the technique itself has been around since the mid-20th century .…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…DoE has been used extensively in the optimization of chemical processes, particularly in pharmaceutical and fine chemical settings. DoE is often used for studies relating to enhancing the yield and purity of particular products but is also used for drug formulations and delivery, analytical method development, and more. This is because there are numerous and undisputed benefits to the use of DoE for experimental parameter screening and optimization, especially when compared with traditional human intuition-guided experimentation. With the rise of user-friendly software packages and the increased awareness of the chemical community, there has been a large uptake of this statistical method in recent years, although the technique itself has been around since the mid-20th century .…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…As is known to all, the structural construction of POMs can be easily influenced by synthetic conditions. , Reviewing the synthesis of those reported two-story polyoxotungstates, it is found that the dosage of the second HA is 1.0–2.9 times of the first HA, while in our work, the molar ratio of the two HAs ([SeO 3 ] 2– : [SbO 3 ] 3– ) is about 5.0 (Table S2). Thus, the larger usage of the second HA is supposed to benefit the formation of the three-story {SbSe 2 W 21 } PBU.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Such an approach, based on the classical "design of experiments" methodology, has recently shown success in the synthesis of complex nanomaterials but has yet to be applied to nanocarbon synthesis mediated by molten salts. [20][21][22][23][24] For molten salt synthesis of carbon nanomaterials, synthetic parameters of importance include the identity of organic precursors and salts; the salt:precursor ratio; and the thermal profile employed during synthesis. Each of these factors is hypothesized to uniquely impact the properties of the resulting carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Such an approach, based on the classical “design of experiments” methodology, has recently shown success in the synthesis of complex nanomaterials but has yet to be applied to nanocarbon synthesis mediated by molten salts. [ 20–24 ]…”
Section: Introductionmentioning
confidence: 99%